2016
DOI: 10.4049/jimmunol.1402681
|View full text |Cite
|
Sign up to set email alerts
|

C1P Attenuates Lipopolysaccharide-Induced Acute Lung Injury by Preventing NF-κB Activation in Neutrophils

Abstract: Recently, ceramide-1-phosphate (C1P) has been shown to modulate acute inflammatory events. Acute lung injury (Arnalich et al. 2000. Infect. Immun. 68: 1942–1945) is characterized by rapid alveolar injury, lung inflammation, induced cytokine production, neutrophil accumulation, and vascular leakage leading to lung edema. The aim of this study was to investigate the role of C1P during LPS-induced acute lung injury in mice. To evaluate the effect of C1P, we used a prophylactic and therapeutic LPS-induced ALI mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 61 publications
(106 reference statements)
2
29
0
Order By: Relevance
“…Modulation of Th17 cells involves P2 signaling and inhibition of P2X7 activation decreases IL-6 levels and STAT-3 effects, both impacting Th17 cell differentiation (44). These mechanisms may act in concert with induction of CD39, which shifts the balance towards P1 adenosinemediated signaling and modulates Th17 cell pathogenic potential (18).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of Th17 cells involves P2 signaling and inhibition of P2X7 activation decreases IL-6 levels and STAT-3 effects, both impacting Th17 cell differentiation (44). These mechanisms may act in concert with induction of CD39, which shifts the balance towards P1 adenosinemediated signaling and modulates Th17 cell pathogenic potential (18).…”
Section: Discussionmentioning
confidence: 99%
“…CerK knockout mice display severe neutropenia, which seems to be due to entrapment of neutrophils in bone marrow . Conversely, C1P administration decreases the pro‐inflammatory state of neutrophils in patients with chronic obstructive lung disease . In human peripheral blood mononuclear cells, C1P suppresses LPS‐mediated production of pro‐inflammatory cytokines, including TNF, interleukin (IL) IL‐6, IL‐8, and IL‐1β, and inhibits TNF‐α converting enzyme, which triggers TNF‐α production …”
Section: Ceramide and Ceramide 1‐phosphatementioning
confidence: 99%
“…Mice also presented decreased levels of pro-inflammatory cytokines IL-1β, IL-6, MIP-1 and the neutrophil chemoattractant CXCL1. Mechanistically, the authors demonstrated that human neutrophils from COPD patients have increased levels of NFkB-driven IL-8 production and the phenotype is reversed with C1P treatment (Baudiss et al, 2015; Baudiss et al, 2016). …”
Section: Sphingolipids In Neutrophil Regulationmentioning
confidence: 99%